Prospek, Problematika dan Strategi Baitul Mal Wat Tamwil (BMT) Al-Karomah Menghadapi Era Disrupsi 5.0 - Muh Rizwan Azzaidi; Sri Nirwana Sarowati Zikri (AS-SABIQUN, 2022)
This study aims to determine how the prospects and problems as well as the development strategy of BMT Al-Karomah. This research is a field research, which was conducted at BMT Al-Karomah. This type of research is descriptive research using a qualitative approach. The results of this study indicate that the prospect of BMT Al-Karamah is to encourage economic growth, absorb labor and employment. The problems with developing BMT are the increase in BMM prices that affect BMT operational costs, public perception and knowledge of BMT is still low, similar business competition and the existence of other financial institutions that have started to follow the BMT system, namely the pick-up ball system. The strategy for developing BMT Al-Karomah is the development of human resources, Product Marketing of BMT Al-Karomah